Relation between psychosomatic disturbances and job stress in video display unit operators. - Santarelli, Lory; Rapisarda, Venerando; Fago, Lucrezia; Vella, Francesca; Ramaci, Tiziana; Ledda, Caterina; Bracci, Massimo (Work, 2019)
BACKGROUND: Some psychosomatic disturbances have been related to protracted video display unit (VDU) use at work, and they may be associated with job stress. OBJECTIVE: This study aimed at assessing the association between psychosomatic disturbances with job-related and subjective stress in 990 VDU. METHODS: Job stress was evaluated by Karasek's Questionnaire, psychological job demands and job decision latitude scores were calculated. Workers were assigned to four categories: high-strain job, low-strain job, active job, and passive job. Subjective perception of stress was evaluated with the Rapid Stress Assessment Scale. RESULTS: None of the psychosomatic disturbances investigated were associated with higher psychological job demands scores, whereas many of them were significantly related to lower job decision latitude scores and high-strain jobs. All psychosomatic disturbances were significantly associated with personal stress. Logistic regression confirms the protective role of job decision latitude on headache, fatigue, intestinal gas, disturbed sleep and the significant role of subjective stress on all psychosomatic disturbances studied. CONCLUSIONS: Whereas subjective stress is harmful, job decision latitude is a protective factor for several psychosomatic disturbances reported by VDU operators. Improvement in the job decision latitude might be a preventive specific measure in work planning to reduce possible stress-related disorders.